PENGARUH KUALITAS MAKANAN PADA MENU BREAKFAST TERHADAP KEPUASAN TAMU DI RESTAURANT JAM BALERO HOTEL PUSAKO BUKITTINGGI - Andika, Cica; Kasmita, Kasmita; Pasaribu, Pasaribu (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this research is to see how big is the influence of food quality variable (X) to guest satisfaction variable (Y) at the jam balero restaurant Pusako Hotel Bukittinggi. The sample of this research were 96 persons using a purposive sampling techinuque. The data collection was done with the questionnaire using likert scale that they are highly capable validity and reliability. This research found that : (1) the food quality in the category good enough (67,70%), (2) Guest satisfaction is placed not satisfied category (60,41%) (3) The food quality influence guest satisfaction as much as 28.9 % and 72.1 % influenced by other factors, likes : price, aspects of marketing, product design, production process, customer feedback. Next t count 6,183 > t table (Â±1.66088) with a significant 0,05, later retrieved the value of 0,234 regression worth t count on sig 6,183 to sig. 0,000 < 0,05. It means every an increase of a unit of the food quality will increase 0,234 unit of guest satisfaction.